Pendaftaran Merek Dagang Produk Sirup Kayu Manis di Kabupaten Kerinci - Prayoga Tayosa; Lili Naili Hidayah (Universitas Jambi, Fakultas Hukum, 2020)
The purpose of this thesis is to find out and analyze what are the factors that cause cinnamon syrup entrepreneurs in the village of Siulak Deras Mudik Gunung Kerinci Subdistrict Kerinci Regency does not register their trademarks and to find out and analyze what the legal consequences of cinnamon syrup entrepreneurs in Siulak Deras Mudik village does not register its trademark. This type of research is empirical juridical. Based on the results of the research, the causal factor for not registering trademarks by Cinnamon Syrup entrepreneurs is the lack of understanding of trademarks, the cost of trademark registration is quite expensive. Furthermore, due to a business not registering its trademark viz. There is no protection of the owner of the trademark rights from acts of piracy, counterfeiting and use of his trademark without permission from the trademark owner. other parties may carelessly use brands that have not been registered for their own benefit. the brand owner will not be safe, so in this case the intellectual ideas that he has to make new innovations for his work become useless because people easily imitate these ideas. If there are legal issues regarding this cinnamon syrup brand then it cannot be resolved through legal channels. Brand which was as a differentiating power is now no longer a differentiating power in trading activities, because everyone can use the brand in a business and competition in the global market. Keywords: brand; registration. Abstrak Tujuan penulisan skripsi ini adalah untuk mengetahui dan menganalisa apa saja yang menjadi Faktor penyebab pengusaha sirup kayu manis di Desa Siulak deras Mudik Kecamatan Gunung Kerinci Kabupaten Kerinci tidak mendaftarkan merek dagangnya dan untuk mengetahui dan menganalisa apa akibat hukum pengusaha sirup kayu manis di desa siulak deras mudik tidak mendaftarkan merek dagangnya. Jenis penelitian adalah yuridis empiris. Berdasarkan Hasil penelitian faktor penyebab tidak didaftarkannya merek dagang oleh pengusaha Sirup kayu manis adalah kurangnya pemahaman mengenai merek, biaya pendaftaran merek yang cukup mahal. Selanjutnya akibat suatu usaha tidak mendaftarkan mereknya yaitu. Tidak ada perlindungi pemilik hak atas merek dari tindakan pembajakan, pemalsuan, dan penggunaan merek miliknya tanpa izin dari pemilik merek. pihak lain bisa sembarangan menggunakan merek yang belum terdaftar untuk keuntungan sendiri. pemilik merek tidak akan aman, sehingga dalam hal ini ide-ide intelektual yang dia punya untuk membuat inovasi baru untuk karyanya menjadi tidak berguna karena orang dengan mudahnya meniru ide-ide tersebut.jika ada persoalan hukum menganai merek sirup kayu manis ini maka tidak bisa di selesaikan melalui jalur hukum.Merek yang tadi sebagai daya pembeda sekarang tidak lagi sebagi daya pembeda dalam kegiatan perdagangan, karena setiap orang dapat menggunakan merek tersebut dalam suatu bisnis dan persaingan di pasar global. Kata-kata kunci : pendaftaran; merek.